Real-life temocillin use in Greater Paris area, effectiveness and risk factors for failure in infections caused by ESBL-producing Enterobacterales: a multicentre retrospective study. Issue 1 (29th December 2022) - Dinh, Aurélien; Duran, Clara; Singh, Simrandeep; Tesmoingt, Chloé; Bouabdallah, Laura; Hamon, Antoine; Antignac, Marie; Ourghanlian, Clément; Loustalot, Marie-Caroline; Pain, Jean Baptiste; Wyplosz, Benjamin; Junot, Helga; et al.
Abstract: Background: Temocillin is a β-lactam that is not hydrolysed by ESBLs Objectives: To describe the real-life use of temocillin, to assess its effectiveness in infections caused by ESBL-producing Enterobacterales, and to identify risk factors for treatment failure. Methods: Retrospective multicentric study in eight tertiary care hospitals in the Greater Paris area, including patients who received at least one dose of temocillin for ESBL infections from 1 January to 31 December 2018. Failure was a composite criterion defined within 28 day follow-up by persistence or reappearance of signs of infection, and/or switch to suppressive antibiotic treatment and/or death from infection. A logistic regression with univariable and multivariable analysis was performed to identify risks associated with failure. Results: Data on 130 infection episodes were collected; 113 were due to ESBL-producing Enterobacterales. Mean age was 65.2 ± 15.7 years and 68.1% patients were male. Indications were mostly urinary tract infections (UTIs) (85.8%), bloodstream infections (11.5%), respiratory tract infections (RTIs) (3.5%) and intra-abdominal infections (3.5%). Bacteria involved were Escherichia coli (49.6%), Klebsiella pneumoniae (44.2%) and Enterobacter cloacae (8.8%). Polymicrobial infections occurred in 23.0% of cases. Temocillin was mostly used in monotherapy (102/113, 90.3%). Failure was found in 13.3% of cases. Risk factors for failure in multivariable analysis were: RTI (aOR 23.3, 95% CI 1.5–358.2) and neurological disease (aOR 5.3, 95% CI 1.5–18.6). Conclusions: The main use of temocillin was UTI due to ESBL-producing E. coli and K. pneumoniae, with a favourable clinical outcome. The main risk factor for failure was neurological disease.